1987
DOI: 10.1111/j.1600-079x.1987.tb00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Delay of the Rhythm of 6‐Sulphatoxy Melatonin Excretion by Artificial Light

Abstract: The purpose of this study was to investigate the effect of bright artificial light exposure on the rhythms of 6-sulphatoxy melatonin and cortisol excretion in urine. Six healthy males were exposed to light (greater than 3,000 lux) from 1900 to 0200 h (sunset 1928 h) on one occasion. The artificial light delayed the onset of 6-sulphatoxy melatonin excretion. On the next evening the onset of 6-sulphatoxy melatonin excretion in normal light/darkness was delayed by 1 h. The timing of the peak excretion of cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…served throughout the resetting trial showed daily phase shifts on the average of 1 to 3 h following each cycle of bright light exposure (Fig. 3), consistent with other one-pulse bright light studies (Kennaway et al, 1987;Bureswa et al, 1991;Laakso et al, 1993;Van Cauter et al, 1994;Hashimoto et al, 1996). The melatonin data from control subjects, all of whom remained in dim lighting and darkness, delayed on the average of -0.2 h per day, consistent with the daily delay expected due to the intrinsic period of the human circadian pacemaker observed in dim lighting conditions (Czeisler et al, 1995a).…”
Section: Response Of the Melatonin Rhythm Measured Throughout A Resetsupporting
confidence: 89%
“…served throughout the resetting trial showed daily phase shifts on the average of 1 to 3 h following each cycle of bright light exposure (Fig. 3), consistent with other one-pulse bright light studies (Kennaway et al, 1987;Bureswa et al, 1991;Laakso et al, 1993;Van Cauter et al, 1994;Hashimoto et al, 1996). The melatonin data from control subjects, all of whom remained in dim lighting and darkness, delayed on the average of -0.2 h per day, consistent with the daily delay expected due to the intrinsic period of the human circadian pacemaker observed in dim lighting conditions (Czeisler et al, 1995a).…”
Section: Response Of the Melatonin Rhythm Measured Throughout A Resetsupporting
confidence: 89%
“…These findings more clearly delineate the rate at which the circadian clock can be delayed in a practical protocol that could be used in the real world. Previous studies utilizing a single bright light pulse ending late at night with subjects waking at their habitual time (sleep episode truncated) have reported phase delays of about 1 hour [ 24 , 25 ]. Studies in which a single long duration bright light pulse (> 6 hours, up to ~10,000 lux) was paired with 2 days of a large delay (>8 hours) in the sleep/dark episode have reported phase delays of up to 3 hours [ 9 , 12 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modest (-30 percent) decreases in evening melatonin levels may reduce melatonin receptor activation, thereby altering functional melatonin responses. In humans, ambient light or magnetic field exposures that influence afternoon/evening melatonin levels also suppress or delay the onset of nocturnal melatonin production (6,(61)(62)(63)(64). The combined reduction of both daytime and nocturnal melatonin secretion would lead to reduced 24-hour melatonin secretion, which could alter immunologic (15,16), oncostatic (13)(14)(15), or antioxidant (17)(18)(19) processes influenced by melatonin.…”
Section: 4mentioning
confidence: 99%